A single-center experience of safety and effectiveness of adjustable intragastric balloon in patients with super obesity - Mohammed S. Khan; Adnan Alzanbagi; Abdulaziz Tashkhandi; Laeeque A. Qurashi; Aly ElBahrawy; AlWahhaj Khogeer; Ghadeer Alhazmi; Ghadeer Monshi; Mohammed K. Shariff (The Saudi Journal of Gastroenterology)
Background: The Spatz3® Intragastric Adjustable Balloon (SAB) offers a novel approach to weight loss in super obese patients [body mass index (BMI) ≥50 kg/m2]. This study evaluates the safety, effectiveness, and predictors of success of SAB in this population. Methods: A retrospective study was conducted at King Abdullah Medical City, Makkah, Saudi Arabia, involving 94 patients with SAB implantation. Weight loss metrics (%EWL, %TBWL), complications, and predictors of adverse events were analyzed. Results: Eleven patients required early SAB removal due to severe symptoms. Complications included gastrointestinal bleeding (3.2%), gastric ulcer/erosion (27.7%), and deflation (5.3%). Significant weight loss was observed at 6 and 12 months. The mean absolute weight loss was 22.03 kg at 12 months, with %EWL of 19.27%. Early weight loss at 3 months predicted long-term success. SAB adjustments did not significantly impact outcomes. Post SAB, 57% of patients proceeded to laparoscopic sleeve gastrectomy (LSG) with rare postoperative complications (2.9%). Conclusion: SAB is safe and effective for patients with BMI ≥50 kg/m2, achieving significant weight loss at 12 months. Early weight loss predicts long-term success, and subsequent LSG can be performed without significant complications. Further research should explore long-term outcomes and comparative analyses.